Analisis Kepuasan Pengguna terhadap Aplikasi Axis Net Menggunakan Metode end User Computing Satisfaction (EUCS) di Kota Purwokerto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The rapid advancement of information technology has increased the adoption of digital service applications, including AxisNet as Axis’s official platform for purchasing data packages, checking balances, and accessing promotional features. However, varying levels of user satisfaction particularly among users in Purwokerto highlight the need for a comprehensive evaluation of the application's service quality. This study aims to measure user satisfaction with AxisNet by applying the End User Computing Satisfaction (EUCS) model, which consists of five key dimensions: content, accuracy, format, timeliness, and ease of use. Data were collected from 114 respondents through a structured questionnaire and analyzed using IBM SPSS, including validity testing, reliability testing, and simultaneous testing. The results indicate that all instruments are valid and reliable. Simultaneously, the five EUCS dimensions significantly influence user satisfaction. Partially, the dimensions of content, accuracy, timeliness, and ease of use demonstrate a positive effect, while the format dimension shows a negative effect, suggesting that improvements are needed in the application's visual design. These findings provide empirical insight into the factors shaping user satisfaction with AxisNet and serve as a strategic reference for enhancing the quality and effectiveness of digital service applications.